PERANAN TAKHRIJ AL-HADITS DALAM PENELITIAN HADITS - Emilia Sari (STIQ al-Lathifiyyah Palembang, 2018)
Theoretically hadith has three important elements, namely Sanad, Matan and Perawi. New Hadith can be set and may be accepted (maqbul) or rejected (mardud) before the condition of the sanad is examined. sSanad plays an important role and determines the value of a hadith because sanad is the value chain of the narrators who deliver a matan while the narrator will determine the status of the hadith. Supporting science to understand the status and level of quality of sanad, rawi, and matan hadith is Takhrij al Hadis. in terms of terminology, Takhrij al Hadis is a way to place the location of the hadith in its original source, along with its sanad and explain its dignity. To be able to assess the quality and quantity of a hadith, research is needed, both from sanad and matan. As for the first step in the study of hadith is Takhrij al-Hadith, which is conducting research using the available primary books, which include all the data in detail and valid. The existence of a very wide distance between the reality of today's Muslims and the Khazanah of the past has caused at least Islamic students who want to learn and master the main references in conducting takhrij activities comprehensively. In this Journal the author explains what Takhrij al Hadis are, History of Takhrij al Hadis, Urgency and benefits, Books needed, and methods used in Takhrij al Hadis.